Comparison Between Conventional Radiography and 3D Volumetric Imaging for Location of Mandibular Canal: In Vivo Study - Rakashree Chakraborty; Aarti Panchbhai; Rahul R Bhowate; Sourav Sen (Wolters Kluwer Medknow Publications, 2017)
Aim: The aim of the study was to evaluate the visibility and location of mandibular canal in the mandibular posteriors using orthopantomography and digitalized volumetric tomography. Material and Methods: Twenty-five patients were included in the study with mandibular posterior edentulous areas, where visibility and location of mandibular canal was assessed using orthopantomography and digitalized volumetric tomography. Both parameters were assessed at the mental foramen, at 1 cm, 2 cm, and 3 cm posterior to mental foramen. Results: The results obtained showed that the mandibular canal was more clearly visible at the mental foramen at 1 cm and 2 cm posterior to the mental foramen using digitalized volumetric tomography, which was statistically significant (P = 0.000). At 3 cm posterior to the mental foramen the visibility of the mandibular canal did not differ among the techniques (P = 0.297). The location of the mandibular canal was obtained in superoinferior dimension in orthopantomography and superoinferior and buccolingual dimension was measured in digitalized volumetric tomography where the mandibular canal was located more inferiorly and lingually in mandible. Conclusion: Digitalized volumetric tomography ( DVT) is advantageous than orthopantomography (OPG) for visibility and location of mandibular canal. The precise location of the mandibular would help in planning for implant placement and other interventions in mandibular posteriors.